Outcome of chemotherapy counseling by pharmacists on psychological effects and self esteem among oncology patients in a government hospital in Malaysia - Periasamy, Ummavathy; Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Ismail, Siti Irma Fadhilah (Malaysian Medical Association, 2015)
Introduction: Chemotherapy is the most common form of treatment among cancer patients. It is also known to cause many physical and psychological side-effects. Objective: This study developed, implemented and evaluated the outcome of a chemotherapy counseling module among oncology patients by pharmacists based on their psychological effects (depression, anxiety) and selfesteem. Methods: A randomized, single blind, placebo controlled study was conducted among 162 patients undergoing chemotherapy in a government hospital in Malaysia. Intervention: Counseling sessions were conducted using the 'Managing Patients on Chemotherapy' module for oncology patients undergoing chemotherapy at each treatment cycle. Outcome: The outcome of repetitive chemotherapy counseling using the module was determined at baseline, first follow-up, second follow-up and third follow-up. Results: The findings revealed that there was significant improvement in the intervention group as compared to the control group with large effect size on depression (p = 0.001, partial η2 = 0.394), anxiety (p = 0.001, partial η2 = 0.232) and self-esteem (p = 0.001, partial η2 = 0.541). Conclusion: Repetitive counseling using the ‘Managing Patients on Chemotherapy’ module was found to be effective in improving psychological effects and self-esteem among patients undergoing chemotherapy.